PERAN KOMUNIKASI ANTARBUDAYA BERBASIS KEARIFAN LOKAL: STUDI HARMONI SOSIAL ANTARA KOMUNITAS ADAT DAN PENDATANG DI KOTA MANADO - Christian Franky Tarandung; Avent Patiro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The city of Manado is an area of rich ethnicity and culture but has difficulties in maintaining good relations between local people and migrants. Local wisdom, such as the philosophy of “Torang Samua Basudara” has a great ability to enhance good intercultural communication but has not been much researched in depth as a way to communicate. This research aims to study the ways of intercultural communication between indigenous people and migrants, discover the contribution of local values in strengthening social unity, and design ways of communication based on local culture. The method used was descriptive qualitative through four steps: initial studies and group discussions, data collection through detailed interviews and observations, data analysis with specific themes, and report writing. Preliminary findings show that barriers in communication, such as prejudice and stereotypes can be overcome by internalizing local cultural values in daily interactions. In conclusion, local wisdom not only serves as a cultural binder but can also be used as an effective intercultural communication strategy to create an open and harmonious society.